Penanganan Stres dan Kesejahteraan Psikologis Pasien Kanker Payudara yang Menjalani Radioterapi di RSUD Dr. Moewardi Surakarta - Karyono Karyono,; Kartika Sari Dewi; Lela TA (MEDIA MEDIKA INDONESIANA, 2008)
Stress management and psychological well-being in breast cancer patient undergoing radiotherapyBackground: Many breast cancer patients suffer low psychological well-being because the disease and radiotherapy. To improve the patient’s psychological well-being, should be good stress management strategy.Objective: The research aimed to examine correlations between stress management strategy and psychological well-being among breast cancer patients, and the effectivity of stress coping to psychological well-being.Method: This study was an correlational study between stress management strategy and the psychological well-being. The subjects consist of 30 breast cancer patients undergoing radiotherapy in Moewardi Hospital of Surakarta. Data were measured using Stress Management Strategy Scale and Psychological Well-being scale. Statistical analysis was simple regression analysis.Result: There was significant correlations between stress coping and psychological well-being on breast cancer patients (r=0.778 and p=0.00). The (R2) was 0.606, which means 60.6% psychological well-being were influenced by stress management strategy.Conclusion: Stress management determines psychological well-being in breast cancer patient undergoing radiotherapy.Keyword: Stress management strategy, psychological well-being, breast cancer patient and radiotherapy.ABSTRAKLatar Belakang: Banyak penderita kanker payudara mengalami penurunan kesejahteraan psikologis karena penyakit dan radioterapi yang dijalani. Untuk memperbaiki kesejahteraan psikologis, dibutuhkan strategi penanganan stres.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan strategi penanganan stres dengan kesejahteraan psikologis pada pasien kanker payudara, dan sumbangan efektif variabel stress coping terhadap kesejahteraan psikologis.Metode: Penelitian korelasional dilakukan dengan variabel prediktor strategi penanganan stres dan kesejahteraan psikologis. Subyek penelitian terdiri dari 30 pasien kanker payudara di RSUD Dr. Moewardi Surakarta yang menjalani radioterapi. Data penelitian diambil dengan Skala Strategi Penanganan Stres (koefisien reliabilitas 0,931) dan Skala Kesejahteraan Psikologis (koefisien reliabilitas 0,941). Analisis regresi sederhana digunakan terhadap data yang ada.Hasil: Ada hubungan antara strategi penanganan stres dengan kesejahteraan psikologis (r=0,778, p=0,00), dengan nilai R2=0,606 yang berarti 60,6% kesejahteraan psikologis ditentukan oleh strategi penanganan stres.Simpulan: Strategi penanganan stres sangat menentukan kesejahteraan psikologis pasien kanker payudara yang menjalani radioterapi.